Magnetic Resonance Imaging of Malformations of Midbrain-Hindbrain. Issue 1 (January 2016) - Abdel Razek, Ahmed Abdel Khalek; Castillo, Mauricio
Abstract : Abstract: We aim to review the magnetic resonance imaging appearance of malformations of midbrain and hindbrain. These can be classified as predominantly cerebellar malformations, combined cerebellar and brain stem malformations, and predominantly brain stem malformations. The diagnostic criteria for the majority of these morphological malformations are based on neuroimaging findings. The predominantly cerebellar malformations include predominantly vermian hypoplasia seen in Dandy-Walker malformation and rhombencephalosynapsis, global cerebellar hypoplasia reported in lissencephaly and microlissencephaly, and unilateral cerebellar hypoplasia seen in PHACES, vanishing cerebellum, and cerebellar cleft. Cerebellar dysplasias are seen in Chudley-McCullough syndrome, associated with LAMA1 mutations and GPR56 mutations; Lhermitte-Duclos disease; and focal cerebellar dysplasias. Cerebellar hyperplasias are seen in megalencephaly-related syndromes and hemimegalencephaly with ipsilateral cerebellomegaly. Cerebellar and brain stem malformations include tubulinopathies, Joubert syndrome, cobblestone malformations, pontocerebellar hypoplasias, and congenital disorders of glycosylation type Ia. Predominantly brain stem malformations include congenital innervation dysgenesis syndrome, pontine tegmental cap dysplasia, diencephalic-mesencephalic junction dysplasia, disconnection syndrome, and pontine clefts.